Ubiquitous post‐peak zircon in an eclogite from the Kumdy‐Kol, Kokchetav UHP‐HP Massif (Kazakhstan): Significance of exhumation‐related zircon growth and modification in continental‐subduction settings. (23rd January 2021) - Skuzovatov, Sergei Yu.; Shatsky, Vladislav S.; Ragozin, Alexey L.; Wang, Kuo‐Lung
Abstract: U–Pb geochronological, trace‐element and Lu–Hf isotopic studies have been made on zircons from ultrahigh‐pressure (UHP) mafic eclogite from the Kumdy‐Kol area, one of the diamond‐facies domains of the Kokchetav Massif (northern Kazakhstan). The peak eclogitic assemblage equilibrated at > 900 °C, whereas the bulk sample composition displays light rare‐earth element (LREE) and Th depletion evident of partial melting. Zircons from the eclogite are represented by exclusively newly formed metamorphic grains and have U–Pb age spread over 533–459 Ma, thus ranging from the time of peak subduction burial to that of the late post‐orogenic collapse. The major zircon group with concordant age estimates have a concordia age of 508.1 ±4.4 Ma, which corresponds to exhumation of the eclogite‐bearing UHP crustal slice to granulite‐ or amphibolite‐facies depths. This may indicate potentially incoherent exhumation of different crustal blocks within a single Kumdy‐Kol UHP domain. Model Hf isotopic characteristics of zircons (εHf (t) +1.5 to +7.8, Neoproterozoic model Hf ages of 1.02–0.79 Ga) closely resemble the whole‐rock values of the Kumdy‐Kol eclogites and likely reflect in situ derivation of HFSE source for newly formed grains. The ages coupled with geochemical systematics of zircons confirm that predominantly late zircon growth occurred in Th–LREE‐depleted eclogitic assemblage, that experienced incipient melting and monazite dissolution in melt at granulite‐facies depths, followed by amphibolite‐facies rehydration during late‐stage exhumation‐related retrogression.